“A room full of strangers every day”: the psychosocial impact of developmental prosopagnosia on children and their families - Dalrymple, Kirsten A.; Fletcher, Kimberley; Corrow, Sherryse; das Nair, Roshan; Barton, Jason J.S.; Yonas, Albert; Duchaine, Brad (Elsevier, 2014)
Objective: Individuals with developmental prosopagnosia (‘face blindness’) have severe face recognition difficul¬ties due to a failure to develop the necessary visual mechanisms for recognizing faces. These difficulties occur in the absence of brain damage and despite normal low-level vision and intellect. Adults with developmental prosopagnosia report serious personal and emotional consequences from their inability to recognize faces, but little is known about the psychosocial consequences in childhood. Given the importance of face recognition in daily life, and the potential for unique social consequences of impaired face recognition in childhood, we sought to evaluate the impact of developmental prosopagnosia on children and their families.